Investigation of the Protective Effects of Dexmedetomidine, Midazolam, Propofol, and Intralipid on Oxidative Stress and Inflammation in Rats with Lidocaine-Induced Toxicity - Kucun MK; Guler EM; Saracoglu A; Yildirim M; Demirtas C; Serdogan F; Beyaztas H; Aktas S; Kacan M; Gaszynski T; Ratajczyk P; Saracoglu KT (Journal of Inflammation Research)
Mustafa Kemal Kucun,1 Eray Metin Guler,2,3 Ayten Saracoglu,4 Mehmet Yildirim,5 Cumaali Demirtas,5 Ferda Serdogan,6 Hakan Beyaztas,2,7 Selman Aktas,8 Merve Kacan,9 Tomasz Gaszynski,10 Pawel Ratajczyk,10 Kemal Tolga Saracoglu11 1Department of Anesthesiology and Intensive Care, Bartin State Hospital, Bartin, Turkey; 2Department of Medical Biochemistry, Hamidiye Faculty of Medicine, University of Health Sciences Turkey, Istanbul, Türkiye; 3Department of Medical Biochemistry, Hamidiye Institute of Health Sciences, University of Health Sciences Turkey, Istanbul, Türkiye; 4Department of Anesthesiology, ICU & Perioperative Medicine Aisha Bint Hamad Al Attiyah Hospital HMC, Doha, Qatar; 5Department of Physiology, Hamidiye Faculty of Medicine, University of Health Sciences, Istanbul, Turkey; 6Department of Anesthesiology and Intensive Care, Turhal State Hospital, Tokat, Turkey; 7Department of Medical Biochemistry, HaydarpasaNumune Health Application and Research Center, University of Health Sciences Turkey, Istanbul, Türkiye; 8University of Health Sciences, Hamidiye Faculty of Medicine, Department of Biostatistics and Medical Informatics, Istanbul, Turkey; 9Department of Anesthesiology and Intensive Care, Kocaeli City Hospital, Kocaeli, Turkey; 10Department of Anesthesiology and Intensive Therapy, Medical University of Lodz, Lodz, Poland; 11Department of Anesthesiology, ICU & Perioperative Medicine Hazm Mebaireek General Hospital HMC, Industrial Area Ar-Rayyan, Doha, QatarCorrespondence: Mustafa Kemal Kucun, Department of Anesthesiology and Intensive Care, Bartın State Hospital, Bartın, Turkey, Email mustafakemalkucun@hotmail.comAim: The aim of this study was to compare the effects of dexmedetomidine, midazolam, propofol, and intralipid on lidocaine-induced cardiotoxicity and neurotoxicity.Methods: Forty-eight male Sprague-Dawley rats were randomly divided into six groups (n = 8 per group): control (C), lidocaine (L), lidocaine + dexmedetomidine (LD), lidocaine + midazolam (LM), lidocaine + propofol (LP), and lidocaine + intralipid (LI). Dexmedetomidine (100 μg/kg), midazolam (4 mg/kg), propofol (40 mg/kg), and intralipid (10 mg/kg) were administered intraperitoneally as pretreatment. Lidocaine (90 mg/kg) was administered intraperitoneally to induce oxidative stress in all groups except the control. After 60 minutes of electrocardiography (ECG) recording, the rats were sacrificed, and heart and brain tissue samples were collected. Comparative measurements of total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and inflammatory parameters were conducted.Results: In heart tissue samples, TAS was significantly higher in LI and LD groups (p < 0.05). Additionally, oxidative stress was significantly higher in the LM group (p < 0.05). Despite an increase in oxidative stress in brain tissue samples across all groups, it was found that all groups exhibited antioxidant protective effects (p < 0.05). Inflammatory parameters in heart and brain tissues significantly decreased in all groups, especially in the LI group (p < 0.05).Conclusion: It was observed that pretreatment with midazolam increased oxidative stress induced by lidocaine, while dexmedetomidine and intralipid exhibited greater antioxidant effects. Dexmedetomidine and intralipid used as pretreatment were shown to be more effective in protecting against oxidative stress and inflammation.Keywords: oxidative stress, inflammation, dexmedetomidine, midazolam, propofol, intralipid